The EFFECT OF FOOT MASSAGE ON ANXIETY IN AMI PATIENTS AT RSUD DR. MOEWARDI - Setiawan, Arif Adi; Rahayu, Budi (Jurnal Keperawatan Respati Yogyakarta, 2021)
Cardiovascular disease is the number one cause of death in the world. In Indonesia the incidence of heart disease by 1.5% of the total population of Indonesia and heart disease often encountered is AMI. Patients with AMI experience anxiety can be a contributing factor of complications such as recurrent heart attack and heart failure. Anxiety can be overcome by anxiety management both pharmacology and non-pharmacology, one of the non-pharmacological techniques are relaxation techniques such as foot massage. This study aims to determine the effect of foot massages on anxiety in AMI patients at RSUD Dr. Moewardi. This research design uses a quasi-experimental design with one group pretest and posttest design without control group approaches. The number of samples is 30 respondents with the purposive sampling technique. The results of the study showed that there was an influence of foot massages on anxiety reduction in AMI patients with a p-value <0.05.Anxiety in AMI patients after a foot massage immersed in a decrease from anxiety score of 38,13 to 59,83. Foot massage can stimulate the central nervous system and thalamus in the release of endorphins, causing relaxation. Keywords: Foot Massages; Massage; AMI; Anxiety; Relaxation